A synergistic strategy for fabricating an ultralight and thermal insulating aramid nanofiber/polyimide aerogel. (12th November 2020) - Zhang, Xinhai; Ni, Xingxing; He, Meiyun; Gao, Yujie; Li, Chenxi; Mo, Xiaoliang; Sun, Gang; You, Bo
Abstract : A synergistic strategy was proposed to fabricate an ultralight aramid nanofiber/polyimide (ANF/PI) composite aerogel (5.18 mg cm −3 ), which was highly compressible and low thermal conductivity (28.6 ± 0.53 mW (m K) −1 ). Abstract : Shortcomings of the otherwise very desirable ultralight nanocomposite aerogels urgently need to be solved, such as the poor compatibility of different components, low thermal decomposition temperature, and low production. Herein, a synergistic strategy using ultrahigh-speed homogenizing, freeze drying, and high-temperature imidization methods was proposed to fabricate an ultralight aramid nanofiber/polyimide (ANF/PI) composite aerogel from aramid nanofibers and water-soluble polyamide acid salt, which possess similar chemical structures. The polyamide acid salt greatly inhibited the aggregation of aramid nanofibers without any additional dispersant due to hydrogen bond interactions. The uniform aramid nanofiber skeleton decreased the shrinkage of the low concentration of polyamide acid salt during imidization. This synergistic effect contributed to the porous structure and ultralow density (5.18 mg cm −3 ) of the ANF/PI nanocomposite aerogel. The aerogel showed excellent elasticity, fatigue resistance (1000 compressive cycles), high thermal decomposition temperature (470 °C), and ultralow thermal conductivity (28.6 ± 0.53 mW (m K) −1 ). Therefore, it has excellent application prospects in various fields, including heat management, thermal insulation, lightweight construction, water treatment, and vibration or shock energy damping, especially in harsh environments.